2004
DOI: 10.1007/978-3-540-27860-3_22
|View full text |Cite
|
Sign up to set email alerts
|

Decoupled Interconnection of Distributed Memory Models

Abstract: Abstract. In this paper we present a framework to formally describe and study the interconnection of distributed shared memory systems. In our models we minimize the dependencies between the original systems and the interconnection system (that is, they are decoupled) and consider systems implemented with invalidation and propagation. We first show that only fast (i.e. wait-free) memory models can be interconnected. We then show that causal and pRAM systems can be interconnected if they fulfill some restrictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…They further defined a formal framework to describe the interconnection of distributed shared memory systems in [9] and showed that only fast memory models can be interconnected, where read and write operations return immediately after only local computations (i.e. no global synchronization, which is required to implement SC systems).…”
Section: Related Workmentioning
confidence: 99%
“…They further defined a formal framework to describe the interconnection of distributed shared memory systems in [9] and showed that only fast memory models can be interconnected, where read and write operations return immediately after only local computations (i.e. no global synchronization, which is required to implement SC systems).…”
Section: Related Workmentioning
confidence: 99%